The Behavior of Online Museum Visitors on Facebook Fan Page of the Museum in Indonesia - Arta Moro Sundjaja; Ford Lumban Gaol; Sri Bramantoro Abdinagoro; Bahtiar S. Abbas (Bina Nusantara University, 2017)
The objective of this research was to discover the behavior of museum visitors on Facebook fan page in Indonesia based on the user motivation, user expectation, online community involvement, and Facebook fan page of the museum. This research used a quantitative approach to descriptive analysis. The population was the Facebook users who had followed the Facebook fan page of the museum in Indonesia. The samples used were 270 respondents. The researchers distributed the questionnaire to a Facebook group managed by museums or communities. Based on the demographic profile of respondent, the researchers discover that the respondents are highly educated, work as employees or student, and allocate more than Rp500.000,00 per month for traveling expense. Based on social media behavior of the respondents, the respondents are active using Facebook and not aware of the presence of museum in social media. The respondents require museum information, social interaction, and entertainment on Facebook fan page of the museum. Therefore, museum managers must maintain the content quality and perceived usefulness in delivering the information through Facebook. The involvement of cultural community can help people to get honest information about museum through credible opinion from the respondents.